2022
DOI: 10.1007/s10705-021-10190-1
|View full text |Cite
|
Sign up to set email alerts
|

Slurry acidification outperformed injection as an ammonia emission-reducing technique in boreal grass cultivation

Abstract: Ammonia (NH3) constitutes the single largest loss of manure nitrogen (N), making measures targeted at reducing its emissions meaningful for the environment and the overall efficiency of manure N use. In this study, the performance of two emission-reducing techniques, acidification and injection, were studied in a field experiment with grass ley over two growing seasons. Emissions of NH3, crop growth, and N use efficiency were determined from plots fertilized with cattle slurry either band spread, injected or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Hence, a N deficiency, rather than a lack of P, caused the yield decrease observed in the PS treatment. Moreover, a loss because of ammonia volatilization in the surface application of slurry reduced N utilization in the PS treatment compared with mineral N (Keskinen et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a N deficiency, rather than a lack of P, caused the yield decrease observed in the PS treatment. Moreover, a loss because of ammonia volatilization in the surface application of slurry reduced N utilization in the PS treatment compared with mineral N (Keskinen et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Slurry acidification is an efficient technique to reduce NH 3 volatilization (Keskinen et al, 2022); however, its effect on N 2 O emission is not consensual as enhancing effects (Gómez‐Muñoz et al, 2016), no effects (Malique et al, 2021), and mitigating effects (Owusu‐Twum et al, 2017; Park et al, 2018) have been observed. Furthermore, the results of slurry acidification on soil microbial structure and function, Mineral Fertilizer Replacement Value (MFRV) and herbage yields, particularly in permanent grasslands, are unclear due to limited research (Fangueiro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%